2001
DOI: 10.1074/jbc.m010907200
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Partially Folded Intermediate in α-Synuclein Fibril Formation

Abstract: Intracellular proteinaceous aggregates (Lewy bodiesand Lewy neurites) of ␣-synuclein are hallmarks of neurodegenerative diseases such as Parkinson's disease, dementia with Lewy bodies, and multiple systemic atrophy. However, the molecular mechanisms underlying ␣-synuclein aggregation into such filamentous inclusions remain unknown. An intriguing aspect of this problem is that ␣-synuclein is a natively unfolded protein, with little or no ordered structure under physiological conditions. This raises the question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

119
1,177
6
8

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,070 publications
(1,310 citation statements)
references
References 47 publications
119
1,177
6
8
Order By: Relevance
“…[20][21][22][23][24][25][26] This suggests that many IDPs undergo a structural change with increasing temperature. Different models have been put forward to explain this observation; however, the data do not decisively determine which explanation is correct, mainly because of the lack of atomic resolution information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22][23][24][25][26] This suggests that many IDPs undergo a structural change with increasing temperature. Different models have been put forward to explain this observation; however, the data do not decisively determine which explanation is correct, mainly because of the lack of atomic resolution information.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies have identified structural changes upon heating that were interpreted mostly as formation of a-helices and to a minor extent to a loss of PPII structure. [20][21][22][23][24][25][26] The interpretation of the changes observed by CD spectroscopy is ambiguous. This is caused by the low resolution of this technique and the fact that structural changes in different segments may have spectroscopic contributions that cancel each other's signal.…”
Section: Introductionmentioning
confidence: 99%
“…In such species, the peptide or protein involved exposes at least part of its main chain and hydrophobic residues to the solvent under conditions in which intermolecular interactions can take place. In the case Textbox 1 of globular proteins, the formation of amyloidogenic intermediates involves the disruption of the native structure to a greater or lesser extent [18][19][20]; in natively unfolded proteins or unstructured peptides, this step may involve the formation of partially folded species with a high propensity to aggregate [21,22]. The second step is the self-association of the Fig.…”
Section: The Generic Nature Of the Amyloid Structurementioning
confidence: 99%
“…When isolated in dilute solution at neutral pH, the protein shows a primarily disordered conformation without a well defined secondary or tertiary structure, 29 although both nascent secondary structure preferences 30 and transient tertiary interactions 31,32 are detectable. At Low pH, however, aS has been reported to adopt a more compact conformation with altered secondary structure content, 33 and the formation of this low pH intermediate conformation is maximal at pH 3.0. 33,34 At the same time, low pH accelerates aS fibril formation, indicating that the induced conformational changes favor fibril formation.…”
Section: Introductionmentioning
confidence: 99%
“…At Low pH, however, aS has been reported to adopt a more compact conformation with altered secondary structure content, 33 and the formation of this low pH intermediate conformation is maximal at pH 3.0. 33,34 At the same time, low pH accelerates aS fibril formation, indicating that the induced conformational changes favor fibril formation. Here we present a detailed study of the conformation of aS at pH 3.0, using NMR secondary chemical shifts, paramagnetic relaxation enhancement, and residual dipolar couplings.…”
Section: Introductionmentioning
confidence: 99%